2011
DOI: 10.1111/j.1551-2916.2011.04928.x
|View full text |Cite
|
Sign up to set email alerts
|

Y2O3–MgO–ZrO2 Infrared Transparent Ceramic Nanocomposites

Abstract: Increased strength and improved erosion resistance are required for future infrared windows working in harsher mechanical and thermal environments than those used today. In this study, Y2O3–MgO–ZrO2 composite nanopowders were synthesized using a sol–gel combustion process. The fully dense Y2O3–MgO–ZrO2 nanocomposites were prepared by pressureless sintering of the nanopowders at 1400°C for 2 h, followed by hot isostatic pressing at 1350°C for 1 h. The effects of ZrO2 concentration on the microstructure, infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Y 2 O 3 –MgO nanocomposite was recently reported to have excellent mid-infrared transmittance over three- to seven-micrometer wavelength ranges with improved mechanical properties over that of pure yttria and magnesia polycrystalline dense ceramics [10,11,12,13]. However, harsher mechanical and thermal environments have imposed more stringent requirements for improved mechanical strength and optical properties of infrared transparent windows and domes.…”
Section: Introductionmentioning
confidence: 99%
“…Y 2 O 3 –MgO nanocomposite was recently reported to have excellent mid-infrared transmittance over three- to seven-micrometer wavelength ranges with improved mechanical properties over that of pure yttria and magnesia polycrystalline dense ceramics [10,11,12,13]. However, harsher mechanical and thermal environments have imposed more stringent requirements for improved mechanical strength and optical properties of infrared transparent windows and domes.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches such as sol‐gel, combustion, and flame pyrolysis techniques have been employed to synthesize MgO‐Y 2 O 3 nanopowders . Among these methods, the combustion method has become the most efficient choice in case of large‐scale economical production of nanopowders.…”
Section: Introductionmentioning
confidence: 99%
“…And the transmittance can be significantly increased when the grain size is substantially smaller than the incident light wavelength. In general, the reduced grain size will increase the optical transparency of the nanocomposite ceramics by reducing the light scattering at grain boundaries . In addition, according to the Petch equation, the mechanical strength decreases with the increase of grain size, so the reduced grain size will also improve the mechanical strength of the composite nanoceramic, and the increased mechanical strength will further increase the thermal shock resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the reduced grain size will increase the optical transparency of the nanocomposite ceramics by reducing the light scattering at grain boundaries. [6][7][8] In addition, according to the Petch equation, the mechanical strength decreases with the increase of grain size, so the reduced grain size will also improve the mechanical strength of the composite nanoceramic, and the increased mechanical strength will further increase the thermal shock resistance. It has been reported that the Y 2 O 3 -MgO nanocomposite ceramic is transparent in the mid-IR wavelength range, and the thermal shock resistance of Y 2 O 3 -MgO nanocomposite ceramic is higher than most of other mid-infrared window materials.…”
Section: Introductionmentioning
confidence: 99%